TUHANNYA KAUM SUFI - Ahmad . (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
The suhsts accept the notion that God is perfect and the source of pcrfection. IJe is the aim of life, wherever tle source is, no matter it is opposed, expressed with imphed and beautifirl sentences for the sufists. God and human is one; they assume that God cannot be separated from himself.